Impact of Foot and Mouth Disease on cattle production in Peninsular Malaysia - Mohamad, Abdullah; Shaari, Nur Fatihah; Hamzah, Hanny Zurina (Universiti Malaysia Terengganu, 2023)
Foot and mouth disease is vital in Malaysia with increasing yearly cases. Quantitative information about the impact of the disease on the cattle in the country, however, is scarce. This study quantitatively assesses the direct economic impacts of foot and mouth disease outbreaks on cattle production in Peninsular Malaysia. The impacts were assessed based on the data obtained from case outbreaks of cattle in 2017 and 2018. Data were collected using a questionnaire administered to 349 cattle farmers in six states of Peninsular Malaysia from April to October 2018. Collected data were analyzed using a t-test (i.e., to compare between gender within the age of breed) and one-way ANOVA (i.e., to compare between breeds and between ages within the breed). Results demonstrate that the breed of Limousine, Charolaise and Kedah-Kelantan have been proven affected due to the FMD outbreak. The economic losses of foot and mouth disease outbreaks due to mortality and weight loss reached the figure of MYR390.24 per herd. To reduce the impact of the loss of cattle production and achieve Malaysia food security target, it is vital for the government to surveillance and eradicates FMD outbreak.